Effectiveness of herbicides against weeds and their residual effect on soil and carrot (Daucus carota) - PANGHAL, V P S; DUHAN, ANIL; DUHAN, D S; RANI, POOJA (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted to study the efficacy of different herbicides for weed control in carrot (Daucus carota L.) and their residual effect on soil as well as on crop, at Research Farm of CCS Haryana Agricultural University, Hisar (2012–13 and 2013–14). Thirteen treatments includes pre-emergence application of three herbicides, viz. oxyfluorfen and oxadiargyl (80, 100, 120 g/ha and 100 g/ha + HW), and pendimethalin (1.0 kg/ha and 1.0 kg/ha + HW), two weedings at 30 and 60 DAS, weed free and weedy check (control) are replicated three times in Randomized Block Design. Residues of these herbicides were estimated in soil and root samples, using GC-MS/MS. Based on two years pooled data it was concluded that pre-emergence application of oxadiargyl 100 g/ha, oxyfluorfen 100 g/ha and pendimethalin 1.0 kg/ha integrated with one hand weeding at 30 DAS resulted in effective weed control (70–72%) in carrot without any phytotoxicity on crop and gave 79.5, 77.2 and 76.4% higher root yield over weedy check, respectively. The residues of these herbicides in soil, carrot root as well as in foliage were found below detectable level at the time of harvest.